Efficacy of Dried Distiller’s Grains with Solubles as a Replacement for Soybean Meal in the Rations of Growing Goats - Sihag, Sajjan; Sihag, Zile Singh; Shunthwal, Jyoti; Kumar, Sushil (Indian Journal of Animal Nutrition, 2017)
The effect of replacement of soybean meal (SBM) by dried distiller’s grains with solubles (DDGS) at different levels in the concentrate mixture on growth performance and nutrient utilization in goat’s kids was studied. Twenty four crossbred weaned female crossbred kids (4-5 mon.) with an average body weight 10.63±0.67 kg were divided into four groups of six animals each. All the kids were fed gram straw ad lib. and weighed quantity of concentrate mixture as per their nutrient requirements. The concentrate mixture (% parts: maize 50, barley 19, soybean meal 28, mineral mixture 2 and common salt 1) was fed to control group (T1) while SBM of control group was replaced with DDGS @ 50, 75, and 100% (CP basis) in the concentrate mixture of groups T2, T3 and T4, respectively. The experiment lasted for 120 days. A digestion trial of 6 d duration was conducted at the end of the study. Average DM intake (DMI) during the feeding trial was 458, 456, 455 and 457 g/d in groups T1, T2, T3 and T4, respectively and DMI as percent of body weight was 2.93, 2.85, 2.94 and 2.94 in the respective groups revealing that DMI was not affected by different levels of DDGS. Average daily gain (ADG) was 58.7, 59.7, 57.6 and 56.0 g in groups T1, T2, T3 and T4, respectively. The daily weight gain and total weight gain by the goat kids were also not affected up to 75% replacement level but decreased (P<0.05) at 100% replacement level. The digestibility of DM, OM, EE, CF and NFE was similar in all the groups, however, digestibility of CP and CF decreased (P<0.05) in group T4. The DCP and TDN intake and nutritive value of ration was not influenced by replacing soybean meal with DDGS at 75% level in concentrate mixture. Feed conversion efficiency was also similar in all the groups. There was net saving of ` 8.9 and 9.6 per kg weight gain on replacing soybean meal with DDGS at 50 and 75% levels, respectively. It was concluded that DDGS can be used as a protein source to replace 75% soybean meal in diets of growing goats to economize rations.